Sanitary Test of Penyetan Vendors’ Plates Using Swab Test Method of Total Plate Count and Escherichia coli in Tambaksari District of Surabaya - Mulyono, Tiara Puswarni; Hartati, Fadjar Kurnia; Djauhari, Arlin Besari (Universitas Dr Soetomo, 2019)
The number of female workers has been on the rise along with life necessities. The usual role of women to cook for the family gradually transforms into preparing for customers on street foods. Penyetan is one of the favourite kind of street foods due to its availability and extensive selection of side dish options. The plate is standard dishware used to serve penyetan. One plate typically used to serve many customers one after another with the washing process in between. This research serves the purpose of finding out the hygiene of the street foods in Tambaksari, Surabaya, using the presence of Escherichia coli bacteria as a marker towards 76 penyetan street foods in Tambaksari district. From 76 places, the result showed that only eight places (11%) meet the requirements of the Health Minister Regulation No. 1096/2011 about Hygiene Sanitation for Catering Services, while the other 68 plates (89%) contained bacteria that surpass the threshold of the regulation. And for E. coli, the result was 20% (15 places) are positive, while the other is negative (80% or 61 places).The number of female workers has been on the rise along with life necessities. The usual role of women to cook for the family gradually transforms into preparing for customers on street foods. Penyetan is one of the favourite kind of street foods due to its availability and extensive selection of side dish options. The plate is standard dishware used to serve penyetan. One plate typically used to serve many customers one after another with the washing process in between. This research serves the purpose of finding out the hygiene of the street foods in Tambaksari, Surabaya, using the presence of Escherichia coli bacteria as a marker towards 76 penyetan street foods in Tambaksari district. From 76 places, the result showed that only eight places (11%) meet the requirements of the Health Minister Regulation No. 1096/2011 about Hygiene Sanitation for Catering Services, while the other 68 plates (89%) contained bacteria that surpass the threshold of the regulation. And for E. coli, the result was 20% (15 places) are positive, while the other is negative (80% or 61 places).